Pengembangan E-LKPD Berbasis Pendekatan Kontekstual Menggunakan Liveworksheet - Sepriasa, Rani; Friyatmi, Friyatmi (Universitas Negeri Padang, 2024)
This research aims to produce E-LKPD that is valid, practical, and effective for use in learning. This type of research is research and development (R&D) with an experimental method through the ADDIE model development procedure. The data gathering strategy includes both testing (posttest) and non-testing methods such as validation sheets, instructor and student questionnaires, and observations. The liveworksheet-based E-LKPD satisfies the requirements for high validity, according to the evaluation of content and media specialists. The post-test findings demonstrate how the experimental and control groups' learning outcomes differed, reveal the effectiveness of E-LKPD based on liveworksheet. The results showed that the E-LKPD developed is valid, practical and effective for use in economics learning.